Multi-scale study of initial tool wear on textured alumina coating, and the effect of inclusions in low-alloyed steel. (August 2016) - Bejjani, R.; Collin, M.; Thersleff, T.; Odelros, S.
Abstract: When turning low-alloyed steel with hard inclusions, scores and grooves have been observed in the wear of the alumina coating in CVD coated cutting tools. This study focuses on detailed understanding of flank wear in the textured alumina coating and the relation to the workpiece׳s inclusions. For chip formation studies, a quick stop device has been used. A topography analysis for the worn coating was performed in the micro scale. Studies at lower scales were performed using TEM. This allowed the study of wear on the coating crystalline structure and the embedment of workpiece material on its surface. Based on the results, the mechanism behind the initial wear was analyzed and an abrasion wear model is proposed. Highlights: Study of tool wear of a textured alumina coating and the relation to the workpiece. A multi-scale approach was used with TEM and 3D surface topography. A quick stop device was developed to study the chip and inclusion effect. A nanocrystalline Al2O3 layer was found on the coating surface. An abrasion wear model was proposed to explain the abrasion mechanism.